Estudio de prefactibilidad para la instalación de una planta de producción de agua de membrillo (Cydonia oblonga) - Barba Claros, Gloria Elena (2016)
The present prefeasibility study evaluates the commercial, technical, economic and financial viability for the installation of a quince water factory in the province of Lima. The demand of the project for the tenth year is 6.608.015 bottles of quince water, with a price of S/. 1,88 per bottle. The factory will be located in Santa Anita district in Lima Metropolitana and it will have a capacity of 983 bottles per hour.